Pengabdian Kepada Masyarakat Melalui Pemanfaatan Sampah Anorganik Rumah Tangga Dengan Metode 4r. - Hasnah Faizah; Isni Juniyati; Nadia Armanda; Rihan Naya Shabilla; Ayuning Jenia Ayunda Putri; Sinta Nur Aliah; Caesara Qanita Supri; Muhammad Berly; Putri Maharani; Muhammad Nabiel; Muhammad Fajri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the themes included in the Kukerta UNRI 2023 activity is the welfare theme particularly in community health and safety programs. Based on the theme and program, the activity performed by Kukerta UNRI in the village of Pulau Terap is devotion to the community through the 4R method of household nonorganic waste utilization. The purpose of this activity is that students are expected to find solutions to health problems, particularly those caused by household garbage, especially in the village of Pulau Terap. The goal is also to educate people on how to manage inorganic household garbage to be more useful products. As for products made in flower pots using fabrics in cloth litter that are widely found in the household. Students do this activity with the two stages of socialization and practice. Socialization involves the poor health impact of garbage, and how the 4R method can provide solutions to the garbage problem. But practice followed by illustrating steps made to create flowerpots from inorganic household garbage.